(Mis)Understanding The Once-and-For-All Rule Member of The Executive Council for Health and Social Development, Gauteng v DZ obo WZ 2018 (1) SA 335 (CC) - André Mukheibir (Obiter, 2019)
The “once-and-for-all” rule (OAFA rule) originated in English law. This rule entails that a plaintiff may not bring more than one action for damages, insofar as this action is based on the same cause of action. The rule has particular significance for prospective loss because where a prospective loss is based on the same cause of action as past loss, the claim for the prospective loss has to be brought at the same time as the claim for past loss. It stands to reason, therefore, that a claim cannot be instituted too soon because the damage arising from the delictual conduct has to be assessed properly. On the other hand, because all delictual claims prescribe after three years, the action for damages has to be brought before three years have passed. Between the OAFA rule and the prescription of a delictual claim, there is not much opportunity for a plaintiff to become aware of the true extent of his or her future loss.The Constitutional Court in Member of the Executive Council for Health and Social Development, Gauteng v DZ obo WZ (2018 (1) SA 335 (CC) (MEC Health)) recently had to consider whether the common law, insofar as it relates to the OAFA rule, should be developed to make provision for instalment or periodic payments. The majority, per Froneman J, held that the law did not make provision for instalment payments but that any amendment to the rule should be left to the legislature. Jafta J, in his minority decision, held that it was not necessary to develop the common law, as it already made provision for instalment payments.The purpose of this note is to show that the majority decision in MEC Health is based on an incorrect understanding of the nature and purpose of the rule, and that the rule does not necessarily exclude periodic or instalment payments. Awarding periodic payments in the case of prospective loss will, furthermore, result in a fairer dispensation, which is also, as is shown below, more aligned with the fundamental principles of the law of delictual damages. Provision is already made for periodic payments in the case of compensation schemes such as the Road Accident Fund Act (56 of 1996) and the Road Accident Benefit Scheme Bill (B17 2017, which will replace the Road Accident Fund Act) and the Compensation for Occupational Injuries and Diseases Act (30 of 1993).